Die Petosiris-Nekropole von Tuna el-Gebel Band 2: Die Häusergruppen 1 und 2, die Südgruppe, Site Management am Grab des Petosiris und Dachentwässerungstechniken - Lembke, Katja; Schlehofer, Jenny H. (Identität und Alterität. Ägypten im Zeitalter der Fremdherrschaften, 2023)
The Petosiris necropolis at Tuna el-Gebel is one of the largest cemeteries of the Roman period in Egypt and belonged to the 'metropolis' Hermopolis Magna. This volume presents new archaeological and architectural-historical research results on the tomb houses of house groups 1 and 2, site management and roof drainage techniques. They provide extensive insights into construction methods, burial customs and ideas of the afterlife in a multicultural society. For the first time, numerous decorated tomb houses are comprehensively published and commented on. This volume was produced as part of the DFG research project "Celebrating with the Dead. Spatial Concepts and Burial Rituals in the Petosiris Necropolis of Tuna el-Gebel/Egypt". With contributions by Hussein Mohamed Ali, Cäcilia Fluck, Jana Helmbold-Doyé, Heidi Köpp-Junk, Katja Lembke, Timo Meyer, Martina Minas-Nerpel, Stefan Pfeiffer, Silvia Prell and Christine Wilkening-Aumann.